Taxonomic review of Cerozodus Bigot, 1857 (Diptera: Asilidae: Asilinae) with the description of two new species - Camargo, Alexssandro; Vieira, Rodrigo; Rafael, José Albertino (Zootaxa, 2022)
In this work, a taxonomic review of Cerozodus Bigot, 1857 is performed and its two included species namely, Cerozodus brachylobus Vieira, Rafael & Limeira-de-Oliveira, 2013 and Cerozodus nodicornis (Wiedemann, 1828) are redescribed and two new species from Brazil are described, Cerozodus ayalai sp. nov. and Cerozodus platylobus sp. nov. Illustrations of male and female, including their respective terminalia are presented. A key for all species is proposed and an updated map with the distribution records is presented.